Improving the Odds in Advanced Breast Cancer With Combination Immunotherapy: Stepwise Addition of Vaccine, Immune Checkpoint Inhibitor, Chemotherapy, and HDAC Inhibitor in Advanced Stage Breast Cancer - Gatti-Mays, Margaret E.; Gameiro, Sofia R.; Ozawa, Yohei; Knudson, Karin M.; Hicks, Kristin C.; Palena, Claudia; Cordes, Lisa M.; Steinberg, Seth M.; Francis, Deneise; Karzai, Fatima; Lipkowitz, Stanley; Donahue, Renee N.; et al. (Frontiers in Oncology, 2021)
Breast tumors harbor low mutational burden, low PD-L1 expression, defective antigen processing, and an immunosuppressive microenvironment (TME). In a malignancy refractory to checkpoint blockade, there is an unmet need for approaches that increase immune infiltration. Preclinical data guided the development of this trial combining (1)BN-brachyury (poxvirus vaccine encoding the tumor associated antigen brachyury), (2)bintrafusp alfa (bifunctional protein with the extracellular domain of the TGF-bRII receptor fused to a human IgG1 anti-PD-L1), (3)entinostat (class I histone deacetylase inhibitor) and (4)T-DM1 (standard of care antibody-drug conjugate targeting HER2). We hypothesize the combination will induce a robust immune response with improved response rates through (1)expanding tumor antigen-specific effector T cells, natural killer cells and immunostimulatory dendritic cells; (2)improving antigen presentation and (3)decreasing inhibitory cytokines, regulatory T cells, and myeloid-derived suppressor cells. In an orthotopic HER2+ murine breast cancer model, tetra therapy induced high levels of antigen-specific T cell responses, tumor CD8+ T cell/Treg ratio, and augmented the presence of IFNg- or TNFa-producing CD8+ T cells and IFNg/TNFa bifunctional CD8+ T cells with increased cytokine production. Based on this data, a phase 1b clinical trial evaluating the stepwise addition of BN-brachyury, bintrafusp alfa, T-DM1 and entinostat in advanced breast cancer was designed. Arm 1(TNBC) receives BN-brachyury+bintrafusp alfa. Arm 2 (HER2+) receives T-DM1+BN-brachyury+bintrafusp alfa. Arm 3 (HER2+) receives T-DM1+BN-brachyury+bintrafusp alfa + entinostat. Reimaging is every 2 cycles (1 cycle = 21 days). Arms 2/3 undergo biopsies at baseline and after 2 cycles to evaluate changes within the TME. Co-primary objectives are response rate and safety. All arms employ a safety assessment in the initial 6 patients and a 2-stage Simon design for clinical efficacy (Arm 1: ≥ 3 responses of 8 expand to 13 patients; Arms 2/3:≥ 4 responses of 14 expand to 19 patients per arm). Secondary objectives include progression-free survival and changes in tumor infiltrating lymphocytes. Exploratory analyses include changes in peripheral immune cells and cytokines. To our knowledge, the combination of a vaccine, an anti-PD-L1 antibody, entinostat and T-DM1 has not been previously evaluated in the preclinical or clinical setting. This trial (NCT04296942) is open at the National Cancer Institute.